Effect of omega-3 and D-chiro inositol compared to D-chiro inositol alone on hormonal parameters in women with insulin resistant polycystic ovary syndrome - Nessa, Amitun; Akter, Sohely; Hossain, Fawzia; Alam, Humaira; Sultana, Rebeka; Ariful Islam, M.; Tarique, Mostafa M. Al; Banu, Jesmine (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Polycystic ovary syndrome (PCOS) is a common endocrine-metabolic disorder marked by high androgen levels, irregular ovulation, and ovarian cysts. Recommended treatments include lifestyle and nutrition changes alongside medication. Omega-3 fatty acids support immune function, insulin sensitivity, cell health, and ovulation. D-chiro Inositol helps lower blood pressure, triglycerides, and glucose, enhances ovarian function, and reduces harmful oxidative stress in the ovaries. This study was designed to evaluate and compare the effect of omega-3 and D-chiro inositol and effect of D-chiro inositol alone on hormonal parameters in women with insulin resistant PCOS. Methods: This randomized controlled trail study was conducted in the departments of reproductive endocrinology and infertility, Bangbandhu Sheikh Mujib medical university, Dhaka from January 2023 to June 2024. Total 60 individuals with PCOS were observed in this study. Results: The mean age was 24.88 (±4.81) years and mean BMI was 28.83 (±2.72) kg/m2. In group A, omega-3 plus D-chiro-inositol therapy is found more effective than D-chiro-inositol alone in reducing serum luteinizing hormone (LH), (follicle stimulating hormone) FSH, free testosterone and fasting glucose, fasting insulin and homeostasis model assessment for insulin resistance (HOMA-IR) after 12 weeks of treatment. But there was no statistically significant difference in post treatment LH, FSH, free testosterone, fasting glucose, fasting insulin and HOMA-IR between 2 groups. Conclusions: Combining D-chiro inositol and omega-3 fatty acids can significantly improve insulin sensitivity and reduce the levels of LH, FSH and free testosterone in women with PCOS. But there is no significant difference in this post treatment hormonal and biochemical parameters between the two groups.